ANALISIS LIKUIDITAS PADA PT. PYRIDAM FARMA Tbk - Subakti, Fajar Eko Kurniawan (EKONOMIA, 2019)
The purpose of this study is to find out and analyze the level of liquidity at PT. Pyridam Farma Tbk from 2013-2017.The theoretical basis used in this study is financial management that focuses on liquidity ratios. The analytical tool used in this study is the liquidity ratio consisting of the current ratio, cash ratio and quick ratio.Data needed, collected by using library research (library research) through collection, recording, and assessment of secondary data in the form of financial statements of PT. Pyridam Farma Tbk in 2013-2017 which has been published on the official website of the Indonesia Stock Exchange (IDX).The results of the research that has been done are Liquidity at PT. Pyridam Farma Tbk in terms of Current Ratio and Quick Ratio in 2013-2017 experienced an increase while in terms of Cash Ratio in 2013-2014 and 2015-2017 it decreased even though in 2014-2015 it increased but still lower than in 2013.